Coin Hoards and Trade in the Seleucid East - Lorber, Catharine C. (Anabasis. Studia Classica et Orientalia, 2022)
Silver coin hoards provide evidence for trade networks in Hellenistic Asia. The evidence is most complete for Syria Seleucis, which provides essential background. Some of the same networks can be detected in more easterly provinces of the Seleucid empire, mostly in the second century. Northern Mesopotamia was perhaps the most commercially active after Syria itself, its trade with Asia Minor sometimes passing through the Armenian Gates rather than through Syria. Susa emerges as a major hub connecting the Iranian plateau with the west. In contrast, Hellenistic coin hoards from the far eastern provinces provide no clear evidence for trade networks, probably because monetary policies restricted the circulation of foreign coinage after the rise of the Bactrian kingdoms.